Model of decision support for the configuration of manufacturing system - Wikarek, Jarosław; Sitek, Paweł; Nielsen, Peter (IFAC-PapersOnLine, 2019)
Manufacturing enterprises today have to face the volatility of markets, characterized by a decreasing production volume and an increasing number of product variants to meet customer expectations. Traditional dedicated manufacturing lines (DML) have been replaced by flexible manufacturing systems (FMS) and, recently, by the systems that combine features of DML and FMS, i.e., by reconfigurable manufacturing systems (RMS). Appropriate manufacturing support and optimization systems for FMS and RMS will advance the quality and effectiveness of reconfigurable manufacturing. This paper proposes an original mixed integer linear programming (MILP) model for decision support in configuration and reconfiguration of the manufacturing system. The modeled problem is a certain development of the known machine loading problem MLP. In this approach, we generate a highly parameterized model based on a set of constraints and a set of questions. Different mathematical programming (MP) - based solvers are proposed to solve this model.